Nigerian Folktales & Other Stories - Nwabia, Kingsley Chibuzor (Nigeria)
Nigerian folktales & other stories is a collection of short stories from both Nigerian and no Nigerian story telling cultures...
Keywords: Folktale; Juvenile Literature; Tales